1972
DOI: 10.3133/pp739
|View full text |Cite
|
Sign up to set email alerts
|

Geology of Isla Desecheo, Puerto Rico, with notes on the great southern Puerto Rico fault zone and Quaternary stillstands of the sea

Abstract: Isla Desecheo is in Mona Passage between Puerto Rico and Hispaniola. The bedrock, 700-1,100 meters of middle Eocene volcaniclastic rocks, consists chiefly of dacitic volcanic sandstone, fine-grained volcanic breccia, and mudstone. Deposition in at least moderately deep water is indicated by the abundance of graded beds and by the fact that interbedded mudstone contains exclusively planktonic faunas. Sparse rounded grains and shallow-water fossil debris in the graded beds indicate that the volcaniclastic debris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

1976
1976
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 4 publications
2
11
0
Order By: Relevance
“…This could be due to a gradual drop of the lake level in the gently-sloping areas, which allows the lake water to remain over the terraces for a longer time and therefore sort the surface deposits better. This is consistent with the conclusion of Seiders et al (1970), who reported that the rapid retreat of sea level allowed the surface deposits of the terraces to remain, while the slow retreat allowed removal and sorting of the terrace deposits by wave-reworking and surface runoff. The existence of a thick layer of fine deposits covering a layer of colluvium in some terraces may indicate a temporal transgression of the lake.…”
Section: Sedimentologysupporting
confidence: 92%
“…This could be due to a gradual drop of the lake level in the gently-sloping areas, which allows the lake water to remain over the terraces for a longer time and therefore sort the surface deposits better. This is consistent with the conclusion of Seiders et al (1970), who reported that the rapid retreat of sea level allowed the surface deposits of the terraces to remain, while the slow retreat allowed removal and sorting of the terrace deposits by wave-reworking and surface runoff. The existence of a thick layer of fine deposits covering a layer of colluvium in some terraces may indicate a temporal transgression of the lake.…”
Section: Sedimentologysupporting
confidence: 92%
“…Pre-Oligocene rocks are known to crop out along the crest and south wall of Desecheo Ridge (Nagle et al, 1978) and form the bulk of Isla Desecheo . Seiders et al (1972) assigned the rocks on Desecheo, which are chiefly deformed dacitic volcanoclastics rocks (volcanic sandstones, mudstones, and conglomerates) with secondary interbedded calcareous foraminiferal mudstones and sandstone, to the Eocene Río Culebrinas Formation. The Río Culebrinas Formation is a unit of the Eocene Cerrillos Belt (Dolan et al, 1991), a sequence of turbidite facies that crops out along the northwest coast of Puerto Rico along the Rincon Peninsula.…”
Section: Morphology and Geologymentioning
confidence: 99%
“…During this time period, and the following 20 million years, two major fault systems, the Great Northern and Southern Puerto Rico fault zones were active, displacing rocks on either side in a left-lateral sense (Briggs, 1968, Seiders et al, 1972 Expected Long-term Seismic Activity…”
Section: Earthquakes and Faults Onlandmentioning
confidence: 99%